Investigating Emotion Perception via the Two-Dimensional Affect and Feeling Space: An Example of a Cross-Cultural Study Among Chinese and Non-Chinese Participants - Lorette, Pernelle (Frontiers in Psychology, 2021)
The categorical approach to cross-cultural emotion perception research has mainly relied on constrained experimental tasks, which have arguably biased previous findings and attenuated cross-cultural differences (Gendron et al., 2018). On the other hand, in the constructionist approach, conclusions on the universal nature of valence and arousal have mainly been indirectly drawn based on participants’ word-matching or free-sorting behaviors, but studies based on participants’ continuous valence and arousal ratings are very scarce. When it comes to self-reports of specific emotion perception, constructionists tend to rely on free labelling, which has its own limitations. In an attempt to move beyond the limitations of previous methods, a new instrument called the Two-Dimensional Affect and Feeling Space (2DAFS) has been developed. The 2DAFS is a useful, innovative and user-friendly instrument that can easily be integrated in online surveys and allows for the collection of both continuous valence and arousal ratings and categorical emotion perception data in a quick and flexible way. In order to illustrate the usefulness of this tool, a cross-cultural emotion perception study based on the 2DAFS is reported. The results indicate cross-cultural variation in valence and arousal perception, suggesting that Russell’s (1995, 2003) minimal universality hypothesis might need to be more nuanced.